SEPARATIST MOVEMENT: UNITED LIBERATION MOVEMENT FOR WEST PAPUA IN PACIFIC ISLAND FORUM 2014-2018 - Sarah Jasmine Az Zahra Sigar (: 2621-0924)
This study aims to determine the pattern of separatist movements that occurred in West Papua in 2014- 2018, this movement is called the United Liberation Movement for West Papua. The internationalization of issues related to human rights violations has become the spotlight of the international community, especially the Pacific Island Forum countries. Vanuatu brought cases of human rights violations in Papua to the UN Council on behalf of the Pacific Island Forum. This separatist movement was formed in Vanuatu, and has the main agenda is solidarity on the equality of Melanesian tribes, cultures and races as well as geographical location between the PIF (Pacific Island Forum) and nearby West Papua. The United Liberation Movement for West Papua (ULMWP) is the place for the aspirations of West Papua votes. The existence of the New York Agreement in 1962 is one of the historical needs of the land of Papua for the transfer of power from the land of Papua from the Netherlands to Indonesia without the participation of representatives from Papua. A lot of support has been made by the Pacific Island Forum countries for the achievement of independence for the Papuan people. This study used a qualitative method, the data collection technique was done by looking for literature reviews, official websites, and primary data from the ULMWP secretariat, as well as official documents as supporting data. Using two helpful and strengthening concepts in this research, the concept of Human Security and Social Movement is used as a reference for developing research. There is a close correlation between Human Security which is based on the freedom to fear to maintain peace and prosperity and human rights violations that have occurred in Papua. The concept of the Social Movement is one of the efforts made by the Pacific Island Forum (PIF) in dealing with human rights issues in Papua until the formation of the United Liberation Movement for West Papua (ULMWP).Keywords: Separatism Movement, United Liberation Movement for West Papua, Human Rights, Human security